DAMPAK PSIKOSOSIAL BENCANA KABUT ASAP PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS PURNAMA - Tio Rita Tambunan; Veny " Elita; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The haze is air pollution (urban air pollution) that contain chemicals harmful to humans and animals. The psychosocial impact make people suffering psychological wounds to the circumstances or social condition. This research puposes to identify the psychosocial impact disaster of smog at Purnama Community Health Centers with retrospective descriptive study design. The sample was 81 respondents taken on the basis of inclusion criteria using purposive sampling technique. Measuring instrument used was a questionnaire Disaster-PAST Methods to enchance Disaster Preparedness, Response and Recovery. The psychosocial impact of haze disaster suffered by people in Purnama Community Health Centers area are anxiety as many as respondents (58%) and depressed behavior as many as 20 respondents (24.7%. Based on the result, we recommend to the next researcher to do the research using qualitative method and for the nurses who work in Purnama Community Health Centers will anticipate the haze disaster. Keywords:  The psychosocial impact, Haze.